EVALUASI KAPASITAS TAMPUNG AIR EMBUNG PADA DAERAH LAYANAN AIR MINUM EMBUNG TIRAWAN KABUPATEN KOTABARU TERHADAP JUMLAH PELANGGAN - Irwan Azhar (INFO-TEKNIK, 2022)
The dry season for the people of Kotabaru is the most difficult period in one year, caused by the phenomenon of water scarcity. Most of the people in Kotabaru very depend on water supply from PDAM. Various efforts to fulfill the community's raw water needs have been carried out such as the construction of the Tirawan reservoir which is expected to be able, for meet the community's raw water needs. In measuring the optimal capacity of the reservoir, it is necessary to calculate the water holding capacity of the reservoir and investigate the area of the Tirawan reservoir. Analysis through rainfall calculation the Log Pearson Type III method. To compare Main capacity and discharge with customer's water requirement, So that it can be seen the service strength of the Tirawan reservoir to meet the water needs of customers during the current dry season and with return periods of 5, 10 and 20 years. The water holding capacity of the Tirawan reservoir is 210,014 m3 with the drainage capacity of the Tirawan reservoir in return periods of 0, 5, 10 and 20 years, to the customer's water demand discharge, respectively, which is Q Flow 0Year = 38.43 m3/s > Q requirement 0 Year = 0, 0632 m3/sec, 5 Year Q Flow = 5 Year Q Flow = 67.34 m3/sec > 5 Year Q requirement = 0.0688 m3/sec, 10 Year Q Flow = 91.97 m3/sec > 10 Year Q Flow = 0.0749 m3/sec and 20 Year Q Flow = 121.03 m3/second > Q20 Year Q requirement = 0.0887 m3/second is estimated to be able to meet customer water needs during the dry season period of 0 Year, 5 Year, 10 Year and 20 Year, respectively, for 92 days, 85 days, 78 days and 66 day.